Mini punch graft for chronic leg ulcers, case series - Angela Mistralina Lukito; Dinda Saraswati Murniastuti; Hajar Imtihani; Niken Trisnowati; Yohanes Widodo Wirohadidjojo (PAGEPress Publications, 2019)
Chronic leg ulcer can caused morbidity and decreased quality of life. Previous study reported leg ulcer affect up to 3% of adult population worldwide Mini punch graft is one of therapeutic options of chronic leg ulcer. This surgical method aimed to include epidermal and dermal tissue with an absence of terminal hair follicles. Previous study mentioned that this procedure stimulated healing in many cases of chronic leg ulcers with total reepithelialization.In this article, the application of multiple mini punch grafts onto two case of extensive leg ulcers caused by burn injury and diabetic ulcer are reported. Split thickness skin graft with mini punch graft require skin donor from inguinal area. The donor were placed onto the ulcer. After several weeks, the ulcer area that had been mini punch grafted show reepethelialization.